2003
DOI: 10.1002/cncr.11489
|View full text |Cite
|
Sign up to set email alerts
|

A survey of intensity‐modulated radiation therapy use in the United States

Abstract: The interfacial area of mass transfer is one of the key parameters in valve tray design, and the valve geometry is the important structural parameter that determines the interfacial area. In this work, the hydrodynamic and mass‐transfer characteristics of three different types of valve trays are investigated. The mechanism of bubbles deformation and breakage in the turbulent dispersion system is theoretically analyzed on the basis of Kolmogoroff's isotropic turbulence hypothesis, and a novel model is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 86 publications
(65 reference statements)
0
38
0
1
Order By: Relevance
“…This is a significant change compared with the survey results reported in 2002, in which 32.1% of radiation oncologists in the United States reported using IMRT. 23 In addition, on a follow-up survey, IMRT use in 2004 was 73.2%; and, of those who were using IMRT, 80.5% used it for head and neck cancers. 24 It also was reported that the adoption rate from 2002 to 2004 was 62.7%.…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant change compared with the survey results reported in 2002, in which 32.1% of radiation oncologists in the United States reported using IMRT. 23 In addition, on a follow-up survey, IMRT use in 2004 was 73.2%; and, of those who were using IMRT, 80.5% used it for head and neck cancers. 24 It also was reported that the adoption rate from 2002 to 2004 was 62.7%.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck (HN) malignancies, IMRT appears to be more and more commonly used for routine treatment, especially in the U.S. [1]. However, only a few randomized trials have demonstrated its superiority over conventional treatments [2] and only a few meaningful retrospective studies are available that demonstrate its potential and its possible drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent survey, nearly 33% of radiation oncologists in the United States stated that they now use IMRT in their clinics, with 80% having implemented IMRT only within the last 1-2 years. 1 Despite the enthusiasm, IMRT remains a new and unproven technology. Although numerous comparisons of IMRT and conventional planning have been presented, outcome studies involving patients who were treated with IMRT are limited.…”
mentioning
confidence: 99%